Game Approach to Improve Dribbling Skills in Basketball Games - Ma'arif, Ilmul (International Journal of Basketball Studies, 2023)
Based on the objectives of this study relating to to determine the approach of the game to improve dribbling skills in basketball games, the method in this study used experimental research methods with the design in this study using a quantitative approach by conducting pre-test, treatment, and post-test, The population of this study was extracurricular basketball students with a total of 35 students, sampling techniques using purposive sampling based on characteristics as students who take part in extracurricular basketball, for data collection using a dribbling ability test in basketball. Data analysis using descriptive tests, hypothesis testing using t-tests to see comparisons based on significant values. The results of descriptive calculations of research data so as to get a minimum score for the pre test 12.11, and post test 11.50, for the maximum pre test 15.32, post test 15.23, for the average pre test 13.32, post test 15.04, and for the standard deviation pre test .98167, post test .90995. calculation of the difference test is obtained from the results of a significant value of 0.023 <0.05, so it can be said that based on the sig value obtained, it can be concluded from the results of the analysis that there is an effect of the game approach on dribbling skill in basketball games.